Reformulation of the Authority of Judicial Commission: Safeguarding the Future of Indonesian Judicial Power - Rasyid, Usman; Nggilu, Novendri Mohamad; Wantu, Fence; Kaluku, Julisa Aprilia; Ahmad, Ahmad (Universitas Negeri Gorontalo, 2023)
Jurisdiction of Indonesian judiciary still leaves various polemics, one of which relates to decisions that are antinomian between the Constitutional Court and the Supreme Court. This research aims to describe efforts to resolve these issues through reformulation within the constitution, regarding the supervisory authority of the Judicial Commission in creating harmonization of judicial decisions in the future. This type of research is normative research. The results indicate that reformulation or redefinition of the authority of the Judicial Commission in the constitution is a gateway to optimizing the role of the Judicial Commission as a product of reform in supervising judges in issuing correct, fair, and legal certainty decisions. Regulation through the constitution is an attributive authority in which the formulation of constitutional norms in the chapter on judicial power, particularly Article of the Judicial Commission, should preferably include phrases of